Ecological Index and Aboveground Biomass Carbon Value on Burn SwampForests After Rehabilitation - Sujatmoko, Sujarwo; Rum, Muhammad; Susanty, Farida Herry; Andriani, Susy; Sopan, Mohamad; Qirom, Muhammad Abdul (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Rehabilitation efforts were conducted in 2018 and 2020 to restore, maintain, and enhance forest and land functions following the 2015 fire on forest area with special purpose (KHDTK) Tumbang Nusa, Central Kalimantan. This study aims to determine the characteristics of stand structure, quantitative ecological values, aboveground biomass values, and preliminary projections of rehabilitation plant valuation in post-fire peat forest ecosystems. Study area was conducted in two rehabilitation blocks in 5 and 7 years old after rehabilitation. Vegetation analysis employed a nested sampling method, utilizing a plot size of 60 x 60 m, with Block I contain three plots (27 subplots) and Block II containing eight plots (72 subplots). Vegetation inventory and four carbon pool measurements were carried out on the understorey, seedlings, saplings, poles, and trees. The stand density value in Block I is 379 stems ha–1 with a basal area of 21.18 m2 ha–1 , while in Block II it is 503 stems ha–1 and 11.27 m2 ha–1 . The stands have good ecological value and stable vegetation, with a medium-scale species diversity level (H' = 1.53–2.80), a low-scale species dominance level (D = 0.10–0.42), commonly a high species richness value (R = 3.07–6.01), and medium to high species evenness values. The composition of rehabilitation plants are similar, but Block I has a higher proportional basal area of 3.72%. The projection of aboveground carbon biomass is 70.7 ton ha–1 and 77.7 ton ha–1 , respectively. As a preliminary study, the effectiveness of the rehabilitation valuation approach can be assessed by the productivity and quantitative ecology.